2004
DOI: 10.1038/sj.mp.4001493
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal symphony: steroid orchestration of gene modules for sociosexual behaviors

Abstract: Genes induced by estrogens in the mammalian forebrain influence a variety of neural functions. Among them, reproductive behavior mechanisms are very well understood. Their functional genomics provide a theoretical paradigm for linking genes to neural circuits to behavior. We propose that estrogen-induced genes are organized in modules: Growth of hypothalamic neurons; Amplification of the estrogen effect by progesterone; Preparative behaviors; Permissive actions on sex behavior circuitry; and Synchronization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 87 publications
0
43
1
Order By: Relevance
“…Previous studies on estrogendependent behavior have identified promising candidate genes. For example, estrogenic regulation of oxytocin signaling is thought to mediate the effects of estrogens on social recognition (44), which could affect aggressive behavior (45). Application of ChIP to identify genes bound by ER␣ in Peromyscus brain samples could be an effective systematic approach to identifying additional pathways that are not yet implicated in the control of social behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on estrogendependent behavior have identified promising candidate genes. For example, estrogenic regulation of oxytocin signaling is thought to mediate the effects of estrogens on social recognition (44), which could affect aggressive behavior (45). Application of ChIP to identify genes bound by ER␣ in Peromyscus brain samples could be an effective systematic approach to identifying additional pathways that are not yet implicated in the control of social behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Primarily on the basis of the results of research by Pfaff and co-workers on lordosis behaviour in rodents, it has been proposed that oestradiol-activated genes in the VMH are organized in five modules referred to as GAPPS modules (Mong and Pfaff, 2004;Pfaff, 2005).…”
mentioning
confidence: 99%
“…The increased synthesis of ribosomal RNA in the ventromedial hypothalamus has been reported to be one of the early effects of oestrogen administered subcutaneously in ovariectomized rats and represents a primary event in the activation of neuronal cells and neuronal pathways involved in female reproductive behaviour (Jones et al, 1990). Oestrogen-driven expansion of dendrites and synapses follows from the stimulation of synthesis of ribosomal RNA (Mong and Pfaff, 2004;Pfaff, 2005).…”
mentioning
confidence: 99%
See 2 more Smart Citations